1998
DOI: 10.1159/000012744
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Training on Zinc Metabolism: Changes in Serum and Sweat Zinc Concentrations in Sportsmen

Abstract: The purpose of this research was to determine the effects of daily physical training on serum and sweat zinc concentrations in professional sportsmen between October and December, during the competing season. Twelve volleyball players and another 12 control subjects have participated in this study. Tests were made in October and December which consisted of a progressive bicycle ergometer test (increasing 30 W every 3 min to reach maximum tolerated power). Blood samples were obtained at rest and immediately aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
41
3
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 35 publications
(70 reference statements)
5
41
3
3
Order By: Relevance
“…Low muscle zinc level will consequently reduce the endurance capacity. 27 Both serum leptin and serum zinc were significantly lower in the elite weightlifters, relative to the control group in our study. The decrease in serum leptin levels may have resulted from long-term regular exercises' increasing fat metabolism and reducing the level of body fat rate, thereby leading to a decrease in plasma leptin.…”
Section: Resultscontrasting
confidence: 41%
“…Low muscle zinc level will consequently reduce the endurance capacity. 27 Both serum leptin and serum zinc were significantly lower in the elite weightlifters, relative to the control group in our study. The decrease in serum leptin levels may have resulted from long-term regular exercises' increasing fat metabolism and reducing the level of body fat rate, thereby leading to a decrease in plasma leptin.…”
Section: Resultscontrasting
confidence: 41%
“…Acute exercise (45,46) and diabetes (3,44) were found to show a marked increase in zinc-supplemented diabetic groups (groups 3 and 6), relative to groups 4, 7 and 8, indicates the importance of zinc supplementation in association with exercise and diabetes. Several researchers showed that serum zinc values decreased after exercise (45,46,47). Elevated levels of zinc we found in zinc-supplemented swimming group (group 5) point out the signifi cance of zinc supplementation in association with exercise.…”
Section: Resultsmentioning
confidence: 89%
“…This fi nding we obtained in group 4 indicates that acute swimming exercise signifi cantly suppresses serum zinc levels. It was argued that daily and regular exercise could be responsible for the impairment in zinc metabolism and that impairments in zinc metabolism as well as zinc loss could lead to muscle exhaustion and weakness (45). Bordin et al (46) demonstrated that physical exercise led to re-distribution of zinc among body stores, blood and tissues, and the increased metabolism caused zinc defi ciency.…”
Section: Resultsmentioning
confidence: 99%
“…Bei Volleyballern konnte man wäh-rend der Trainingsperiode eine progressive Zunahme der Zinkausscheidung im Harn und im Schweiss messen [37]. Auch bei japanischen Soldaten nahm während einer intensiven 24-wöchigen Trainingsperiode die Ausscheidung von Zink und Kupfer im Harn zu [38].…”
Section: Wasser-und Wärmeregulationunclassified